Something’s missing from my education: Using a cross sectional survey to examine the needs and interest of Canadian medical students relating to their roles as teachers and educators - Nagji, Alim; Leslie, Karen; Wong, Eric; Myhre, Doug; Young, Meredith; Chan, Ming-Ka (Canadian Medical Education Journal, 2017)
Background: Current theory in medical education emphasizes engaging learners as educators while tailoring teaching to their learning needs. However, little is known about learners’ perceptions of their proposed roles as teachers and educators. Methods: Canadian medical students were invited to complete an English language online questionnaire structured to include: teaching experience, participation and/or awareness of teacher development at their school and awareness and/or interest in further training in medical education. The survey was developed by the Canadian Association for Medical Education (CAME) Membership Subcommittee, and distributed via the Canadian Federation of Medical Students (CFMS) email list and the CAME twitter account in March 2014. Results: Of the 169 undergraduate medical student respondents, 36% (n=61) reported a lack of prior teaching experience and 45% (n=73) were unsure if their school provided teaching instruction. Overall, 91% (n=150) indicated that they planned to incorporate teaching or medical education into their future careers. Conclusion: While the majority of medical student respondents are expecting or planning to teach, most report not having access to adequate training through medical school. Further effort is necessary to support medical students as teachers to prepare them for increased teaching responsibilities as residents and to expose them to potential careers in medical education.